Avaliação microbiológica da superfície muscular de carcaças ovinas durante as operações de abate em matadouro - Martinelli, Thaís Mioto; Rossi Júnior, Oswaldo Durival [UNESP]; Cereser, Natacha Deboni; Cardozo, Marita Vedovelli [UNESP]; Pinto, Fernanda de Rezende [UNESP]; Perri, Sílvia Helena Venturoli [UNESP] (FUNEP, 2011)
In order to evaluate the hygienic-sanitary conditions of lamb carcasses for human consumption, this study aimed at quantifying populations of indicator microorganisms, such as: mesophiles and psychrotrophs, molds and yeasts, Escherichia coli, Staphylococcus spp. and at identifying pathogenic microorganisms (Salmonella sp. and Listeria spp.). The study was conducted in one lamb slaughterhouse located in the State of São Paulo. Swab samples were collected from muscle surface of forequarter and hindquarter regions of 30 half-carcasses after skinning, evisceration and washing processes. Population counts were between the following values in log10: 2,00 ± 0,32 and 2,59 ± 0,76 UFC/cm2 for mesophiles; 1,52 ± 0,98 and 2,35 ± 1,17 UFC/cm2 for psychrotrophs; 0,75 ± 0,87 and 1,23 ± 0,97 UFC/cm2 for molds and yeasts; 0,00 ± 0,00 and 0,31 ± 0,84 NMP/cm2 for Escherichia coli and 1,75 ± 0,71 and 1,95 ± 0,68 UFC/cm2 for Staphylococcus spp. Salmonella sp. and Listeria spp. were not detected from any of the sampled points. These results indicate the necessity to improve the hygienic-sanitary conditions.

Objetivando avaliar as condições higiênico-sanitárias de carcaças ovinas destinadas à alimentação humana, o estudo consistiu em realizar a quantificação das populações de microrganismos indicadores: microrganismos heterotróficos mesófilos e psicrotróficos, bolores e leveduras, Escherichia coli, Staphylococcus spp. e a identificação de microrganismos patogênicos (Salmonella sp. e Listeria spp.). O estudo foi desenvolvido em matadouro-frigorífico de ovinos, situado no interior do Estado de São Paulo. Foram colhidas amostras, através de swabs, da superfície muscular das regiões dianteira e traseira de 30 meias carcaças ovinas, após as etapas de esfola, evisceração e lavagem. As populações encontradas estiveram entre os seguintes valores em log10: 2,00 ± 0,32 e 2,59 ± 0,76 UFC/cm2 para mesófilos; 1,52 ± 0,98 e 2,35 ± 1,17 UFC/cm2 para psicrotróficos; 0,75 ± 0,87 e 1,23 ± 0,97 UFC/cm2 para bolores e leveduras; 0,00 ± 0,00 e 0,31 ± 0,84 NMP/cm2 para Escherichia coli e 1,75 ± 0,71 e 1,95 ± 0,68 UFC/cm2 para Staphylococcus spp. Salmonella sp. e Listeria spp. não foram detectadas em nenhum dos pontos amostrados. Os resultados indicam a necessidade da melhoria dos cuidados higiênico-sanitários adotados.
Microbiological evaluation of the muscle surface of lamb carcasses during slaughter processes in the slaughterhouse
Keywords: Carcasses; Lamb; Indicator microorganisms; Hygiene; Carcaças; Ovinos; Microrganismos indicadores; Higiene